COOPERATION OF ACADEMICIANS V. M. PERETTS AND M. S. VOZNIAK IN THE LIGHT OF THE EPISTOLARY DOCUMENTS - Andrii Shapoval (Київські історичні студії)
The article analyses the letters of the prominent Ukrainian and Russian philologist V. M. Peretts to the famous Ukrainian literary critic and folklorist M. S. Vozniak. Epistolary documents are stored in the manuscripts department of the V. Stefanyk National Library of Science of Ukraine. The article deals with the professional relations between V. M. Peretts and M. S. Vozniak in the context of the activity of scientists in the Shevchenko Scientific Society in Lviv and the Commission of the Ancient Ukrainian Writing of the All-Ukrainian Academy of Sciences. Attention is drawn to the cooperation of scientists in the field of Ukrainian studies. The cooperation between V. M. Peretts and M. S. Vozniak started from the study of manuscripts from collections stored in Lviv. The article deals with the Ukrainian studies of V. M. Peretеs, which were written by the scientist before the death and have not been published. The negative influence of totalitarian power on the cooperation of Ukrainian scientists is shown. This is the first publication of V. M. Peretts’s letters to M. S. Vozniak. Epistolary documents are a valuable source for the study of the cooperation of Ukrainian philologists in the field of Ukrainian studies in the first half of the twentieth century. The analysis of the letters allows to expand the science philologists circle, to identify the scientists with whom V. M. Peretsz and M. S. Voznsіak collaborated in the field of Ukrainian studies. This creates good prospects for future research.